Viroporins: Structure, function, and their role in the life cycle of SARS-CoV-2. (April 2022) - Breitinger, Ulrike; Farag, Noha S.; Sticht, Heinrich; Breitinger, Hans-Georg
Abstract: Viroporins are indispensable for viral replication. As intracellular ion channels they disturb pH gradients of organelles and allow Ca 2+ flux across ER membranes. Viroporins interact with numerous intracellular proteins and pathways and can trigger inflammatory responses. Thus, they are relevant targets in the search for antiviral drugs. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) underlies the world-wide pandemic of COVID-19, where an effective therapy is still lacking despite impressive progress in the development of vaccines and vaccination campaigns. Among the 29 proteins of SARS-CoV-2, the E- and ORF3a proteins have been identified as viroporins that contribute to the massive release of inflammatory cytokines observed in COVID-19. Here, we describe structure and function of viroporins and their role in inflammasome activation and cellular processes during the virus replication cycle. Techniques to study viroporin function are presented, with a focus on cellular and electrophysiological assays. Contributions of SARS-CoV-2 viroporins to the viral life cycle are discussed with respect to their structure, channel function, binding partners, and their role in viral infection and virus replication. Viroporin sequences of new variants of concern (α–ο) of SARS-CoV-2 are briefly reviewed as they harbour changes in E and 3a proteins that may affect their function.